Effects of Lean Six Sigma application in healthcare services: a literature review - Ahmed, Sellim; Manaf , Noor Hazilah; Islam, Rafikul (Walter de Gruyter, 2013)
The healthcare organization is the place where defects and mistakes cannot be tolerated. A simple mistake can cost a human life so defects or mistakes must be eliminated in healthcare service processes. A Lean Six Sigma (LSS) approach is the best option in a healthcare environment for dealing with a critical patient. The LSS methodology optimizes the average reduction of a desired process. The expected results can be reductions in several aspects of healthcare such as patient waiting time in emergency departments, lost charges for billing in patient financial services, delinquent medical records, diagnostic result turnaround times, accounts receivable days, patients’ length of stay, or medication errors. This paper mainly discusses the effects of the LSS approach in different hospitals around the world according to the literature review. This review also discusses the relationship between LSS as well as their impacts on healthcare services based on literature review.